What is ethics for? - Zavala Sarrio, Salomón (2008)
We present a case of a patient with a frequent condition which poses some ethical problems that may be solved under the guidance of the recent Ethics Code of the Peruvian College of Physicians. We aim to show the practical use of the new Ethics Code.